An overview of aqueous-phase catalytic processes for production of hydrogen and alkanes in a biorefinery - Huber, G.W.; Dumesic, J.A.
In this overview we discuss how aqueous-phase catalytic processes can be used to convert biomass into hydrogen and alkanes ranging from C1 to C15. Hydrogen can be produced by aqueous-phase reforming (APR)of biomass-derived oxygenated hydrocarbons at low temperatures (423- 538 K)in a single reactor over supported metal catalysts. Alkanes, ranging from C1 to C6 can be produced by aqueous-phase dehydration/ hydrogenation (APD/H). This APD/H process involves a bi-functional pathway in which sorbitol (hydrogenated glucose)is repeatedly dehydrated by a solid acid (SiO2-Al2O3)or a mineral acid (HCl)catalyst and then hydrogenated on a metal catalyst (Pt or Pd). Liquid alkanes ranging from C7 to C15 can be produced from carbohydrates by combining the dehydration/hydrogenation process with an upstream aldol condensation step to form C-C bonds. In this case, the dehydration/hydrogenation step takes place over a bi-functional catalyst (4 wt.
Keywords: AQUEOUS-PHASE REFORMING; HYDROGEN PRODUCTION; RENEWABLE ENERGY; FUEL CELLS; AQUEOUS-PHASE PROCESSING; BIO-FUELS